2016
DOI: 10.1142/s2010132516300056
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Capacity Control Capability of Commercial Air Conditioner Units with Variable Speed Compressor

Abstract: The scope of the specific study is the extraction of mathematical relations which correlate the nominal capacity with capacity range of an inverter air conditioner unit with variable speed compressor under standard conditions, that is, measurements of minimum and maximum power of air conditioner under specific indoor and outdoor temperatures. Initially, the necessary statistical information for nominal minimum and maximum capacity will be collected from a sample of 544 different inverter air conditioner models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…An air cooler is developed using a wet layer of material and it is observed that electrical energy consumption is significantly reduced as compared with traditional coolers in [158]. AC efficiency is upgraded by utilizing variable speed compressor [159]. Related to this in [160], it is described that a partial variation in compressor speed leads to more than 10% improvement in the AC energy efficiency.…”
Section: ) Temperature and Humidity Independent Control (Thic)mentioning
confidence: 99%
“…An air cooler is developed using a wet layer of material and it is observed that electrical energy consumption is significantly reduced as compared with traditional coolers in [158]. AC efficiency is upgraded by utilizing variable speed compressor [159]. Related to this in [160], it is described that a partial variation in compressor speed leads to more than 10% improvement in the AC energy efficiency.…”
Section: ) Temperature and Humidity Independent Control (Thic)mentioning
confidence: 99%
“…Therefore, it is necessary to enhance the heat pump system performance in order to make such pumps more energy efficient. Some of the techniques used to improve the heat pump system performance have been used in research [4][5][6][7][8][9]. Vahid et al [10] published a concise review of different control strategies of saving energy in heat pump systems.…”
Section: Introductionmentioning
confidence: 99%